Anaesthetic management in a patient undergoing tooth extraction with a comorbid double outlet right ventricle: A case report - Retti Kartika Bakti; Arie Utariani; Bambang Pujo Semedi (Babcock University Medical Journal, 2025)
Background: This article presents a case of a patient undergoing tooth extraction with general anaesthesia with a comorbidity of double outlet right ventricle (DORV), highlighting anaesthesia considerations for this rare congenital malformation.